Phylum Echinodermata* - Pawson, David L. (Zootaxa, 2007)
The Phylum Echinodermata, comprising approximately 7,000 living species, and 13,000 fossil species, is epitomized by the familiar sea star, a universal symbol of the marine realm. This distinctive group of animals may be briefly defined as possessing a skeleton of calcium carbonate in the form of calcite; a unique water-vascular system which mediates feeding, locomotion, and other functions; and a more or less conspicuous five-part radial symmetry. A closer look at some extant echinoderms will show that some taxa of sea cucumbers lack calcite in their body walls, some taxa of sea stars have “outgrown” five-part symmetry and may have 50 or more arms, and many echinoderms show a more or less conspicuous bilateral symmetry superimposed upon a radial pattern. Fossil echinoderms can be even more puzzling, for some are decidedly asymmetrical, and others may lack evidence of a water-vascular system. Perhaps the only truly reliable taxonomic character of the phylum is that its members today are restricted to the marine realm.